A simple gate driver design for GaN-based switching devices with improved surge voltage and switching loss at 1 MHz operation. (20th October 2020) - Jodo, Shota; Iwaki, Toshihiro; Uchiyama, Kosuke; Islam, Md. Zahidul; Kataoka, Kensuke; Hayakasa, Yuki; Imaoka, Jun; Yamamoto, Masayoshi; Niitsu, Kiichi
Abstract: In power electronics, the impedance of reactance components increases proportionally with frequency; therefore, the sizes of reactance components can be reduced by increasing the switching frequency. Gallium nitride (GaN)-based devices have received significant attention in high-frequency applications because the figure-of-merit of GaN is superior to that of silicon (Si). However, for high-frequency operation, a trade-off relationship between the surge voltage induced by parasitic inductances, and the switching loss becomes significant. Therefore, in this study, we propose a gate driver that improves the trade-off relationship. This gate driver was obtained via the addition of simple logic circuits and capacitors to a conventional gate driver. The effectiveness of our proposed circuit was verified via SPICE simulations with Cadence Spectre using 180 nm CMOS technology. The simulation results show that by operating at 1 MHz, this circuit can help reduce the surge voltage by 12.2% and the switching loss by 14.3%.